ABC success: evidence from ISO 9000 certified companies in Thailand. Issue 3 (26th August 2014) - Intakhan, Phaithun
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the success of activity-based costing (ABC) implementation by confirmatory factor analysis of ISO 9000 certified companies in Thailand. Design/methodology/approach – A structured questionnaire was used to collect data from key participants, accountant managers in ISO 9000 certified companies. Findings – The study confirmed the six constructs for the sample of 102 key participants. The results indicated that ABC implementation success in the context of ISO 9000 certified companies in Thailand consists of upper-management support, ABC system training, non-accounting ownership, links to quality initiative, adequate resources, and links to performance evaluation. Originality/value – The findings have significant implications for ISO 9000 certified companies which intend to adopt or implement ABC. Past findings on ABC implementation success have a small-sample size so they are of limited usefulness. This research has a larger sample size and more carefully chosen participants and so the generalizations are more acceptable.